(untitled) (Research, Society and Development, 2021)
The objective of this study was to investigate whether the use of herbal products as adjuncts to nutritional treatment may help to control visceral fat in overweight / obese individuals. In the development of the research, an integrative review was conducted whose focal issue was to evaluate the efficacy of herbal medicines that are used in the nutritional treatment to control visceral fat. The searches were carried out in the electronic databases, from September 2018 to March 2019. According to the studies found, the major approaches included the use of camellia sinensis (green tea) and its catechins. However, research was also carried out on canola oil, xanthophyll paprika, garcinia cambogia, green coffee, linoleic, linolenic and stearic acids, among others. The results point to positive effects among the researches, which characterizes phytotherapy as an important nutritional strategy in the fight against visceral fat and overweight, especially when combined with dietary reeducation and regular physical activity.